2022
DOI: 10.7150/thno.65522
|View full text |Cite
|
Sign up to set email alerts
|

Targeting protumor factor chitinase-3-like-1 secreted by Rab37 vesicles for cancer immunotherapy

Abstract: Background: Chitinase 3-like-1 (CHI3L1) is a secretion glycoprotein associated with the immunosuppressive tumor microenvironment (TME). The secretory mode of CHI3L1 makes it a promising target for cancer treatment. We have previously reported that Rab37 small GTPase mediates secretion of IL-6 in macrophages to promote cancer progression, whereas the roles of Rab37 in the intracellular trafficking and exocytosis of CHI3L1 are unclear. Methods: We examined the concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Tere have been several studies on colon cancer. associated with the TME, could be a target for cancer therapy [47]. TME plays an important role in nanodrugs and immunotherapy [48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tere have been several studies on colon cancer. associated with the TME, could be a target for cancer therapy [47]. TME plays an important role in nanodrugs and immunotherapy [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez-Lopez et al pointed out that the tumor microenvironment (TME) exerts critical protumorigenic effects through cytokines and growth factors that support cancer cell proliferation, survival, motility, and invasion [ 46 ]. Yang et al demonstrated that CHI3L1, a secretory glycoprotein associated with the TME, could be a target for cancer therapy [ 47 ]. TME plays an important role in nanodrugs and immunotherapy [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In non-muscle cells, actin filaments form a track system to transport cargo such as vesicles and organelles. Recently, it was reported that Rab37 mediated CHI3L1 intracellular vesicle trafficking and exocytosis 44 . Actually, F-actin and the F-actin assembly pathway regulate exocytosis 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Rab37 mediates intracellular vesicle trafficking and exocytosis of chitinase 3-like-1 (CHI3L1), a protumor secretion glycoprotein associated with the immunosuppressive TME, in a GTP-dependent manner which is abolished in the splenocytes and macrophages from Rab37 KO mice. The secreted CHI3L1 activates AKT, β-catenin and NF-κB signal pathways in cancer cells and elicits a protumor TME characterized by activating M2 macrophages and increasing the population of regulatory T cells [75] (exocytosis, Fig. 3A).…”
Section: Vesicles Trafficking Pathways In Macrophagesmentioning
confidence: 99%
“…Importantly, Rab37 colocalizes with IL-2 at the immune synapse, while it colocalizes with TNF in the cytoplasmic compartment in Th1 cells [97]. Of note, Rab37 has recently shown to regulate exocytotic secretion of pro-tumor glycoprotein CHI3L1 from T cell in a GTP-dependent manner to activate M2 macrophages and increase the population of regulatory T cells via activating AKT, β-catenin and NF-kB signal pathways in TME of lung, pancreatic and colon cancers [75] (exocytosis, Fig. 3B).…”
Section: Vesicles Trafficking Pathways In T Cellsmentioning
confidence: 99%